2009
DOI: 10.1073/pnas.0810680105
|View full text |Cite
|
Sign up to set email alerts
|

De novo generation of a transmissible spongiform encephalopathy by mouse transgenesis

Abstract: Most transmissible spongiform encephalopathies arise either spontaneously or by infection. Mutations of PRNP, which encodes the prion protein, PrP, segregate with phenotypically similar diseases. Here we report that moderate overexpression in transgenic mice of mPrP(170N,174T), a mouse PrP with two point mutations that subtly affect the structure of its globular domain, causes a fully penetrant lethal spongiform encephalopathy with cerebral PrP plaques. This genetic disease was reproduced with 100% attack rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
198
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(207 citation statements)
references
References 43 publications
7
198
0
Order By: Relevance
“…They were examined weekly by an individual highly experienced with detecting neurological illness in mice but blinded to the design of the experiments. Importantly, when injected with brain homogenates from aged WT mice, none of the indicator mice developed behavioral or neuropathological abnormalities (14,29). KO mice that do not express PrP were challenged with CJD homogenates and remained healthy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were examined weekly by an individual highly experienced with detecting neurological illness in mice but blinded to the design of the experiments. Importantly, when injected with brain homogenates from aged WT mice, none of the indicator mice developed behavioral or neuropathological abnormalities (14,29). KO mice that do not express PrP were challenged with CJD homogenates and remained healthy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our test for infectivity first used an indicator mouse strain (known as Tga20) that overexpresses PrP and is especially sensitive to prion infection (14,29). At 1 y after injection with CJD homogenates, Tga20 mice became terminally ill with reduced body condition (observed as abnormally loose skin), kyphosis, and a highly unusual gait (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although β2-α2 loop rigidity was thought to potentiate PrP C to PrP Sc conversion (24), subsequent studies revealed that PrP C of species considered resistant to prions, including horses, also contained rigid β2-α2 loops (25)(26)(27). Adding additional complexity, Tg mice expressing mouse PrP C containing rigid β2-α2 loops from elk or horse PrP spontaneously developed prion diseases (28,29). To clarify the effect of the horse PrP β2-α2 loop on prion conversion and to model susceptibility of this at-risk species, we produced Tg mice expressing horse PrP.…”
Section: Significancementioning
confidence: 99%
“…Despite extensive investigations, the physiological function of PrP C in healthy organisms as well as the mechanistic aspects of its pathophysiological role remain elusive (4-9). Although the PrP Sc form found in diseased tissue has been intensively studied, other approaches underline the importance of PrP C as a potential target for TSE prevention and medical intervention after outbreak of the disease (10-12), with a special focus on rigid-loop cellular prion proteins (RL-PrP C s) (11,(13)(14)(15), which are investigated in this paper.A common PrP C fold for a globular domain formed by the polypeptide segment of residues 125-228 in mouse PrP (mPrP) [see Schätzl et al (16) for the numeration in different species], with three α-helices and a short two-stranded antiparallel β-sheet, has been observed for the cellular prion proteins of all mammalian species studied so far (17-27). For WT PrP of most species, parts of the backbone amide group NMR signals of residues in a loop between a β-strand, β2, and a helix, α2, are not observable in NMR spectra recorded with aqueous solutions at pH 4.5 and 20°C at a 1 H resonance frequency of 500 MHz (or higher) because of line broadening by conformational exchange; therefore, the β2-α2 loop in these PrP C s is poorly defined in NMR structures determined under these conditions.…”
mentioning
confidence: 99%